'REFORMATION ON THE RECORD': DEVELOPING THE REFORMATION PROGRAMME AT THE NATIONAL ARCHIVES. Issue 1 (April 2019) - Wilson, Marianne
Abstract : The National Archives holds a wealth of records charting the history and impact of the Reformation in England. Yet whilst many have been mined by scholars, others remain underexploited despite their potential to offer a deeper insight into this period. This article discusses the formation of a programme to increase awareness and engagement: with the public as well as with academic researchers. This involved sharing the skills and knowledge needed to interpret these collections as well as creating Reformationrelated local and regional outreach events and engaging with other archives and heritage institutions.